Reversible Magnesium Metal Anode Enabled by Cooperative Solvation/Surface Engineering in Carbonate Electrolytes - Wang, Caiyun; Huang, Yao; Lu, Yunhao; Pan, Hongge; Xu, Ben Bin; Sun, Wenping; Yan, Mi; Jiang, Yinzhu (Nano-Micro Letters, 2021)
Magnesium metal anode holds great potentials toward future high energy and safe rechargeable magnesium battery technology due to its divalent redox and dendrite-free nature. Electrolytes based on Lewis acid chemistry enable the reversible Mg plating/stripping, while they fail to match most cathode materials toward high-voltage magnesium batteries. Herein, reversible Mg plating/stripping is achieved in conventional carbonate electrolytes enabled by the cooperative solvation/surface engineering. Strongly electronegative Cl from the MgCl2 additive of electrolyte impairs the Mg…O = C interaction to reduce the Mg2+ desolvation barrier for accelerated redox kinetics, while the Mg2+-conducting polymer coating on the Mg surface ensures the facile Mg2+ migration and the effective isolation of electrolytes. As a result, reversible plating and stripping of Mg is demonstrated with a low overpotential of 0.7 V up to 2000 cycles. Moreover, benefitting from the wide electrochemical window of carbonate electrolytes, high-voltage (> 2.0 V) rechargeable magnesium batteries are achieved through assembling the electrode couple of Mg metal anode and Prussian blue-based cathodes. The present work provides a cooperative engineering strategy to promote the application of magnesium anode in carbonate electrolytes toward high energy rechargeable batteries. Highlights: 1 A cooperative solvation/surface engineering approach is reported to achieve the reversible Mg plating/stripping in conventional carbonate electrolytes. 2 Benefitting from the strategy, Mg2+ can easily overcome the reduced desolvation barrier and penetrate the Mg2+-conducting polymer coating, deposited on the Mg metal anode successfully, promoting the application of magnesium anode in carbonate electrolytes toward high-energy rechargeable batteries.